2009
DOI: 10.1007/s11771-009-0010-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of K3Fe(CN)6 in water-in-oil microemulsion

Abstract: A water-in-oil (W/O) microemulsion composed of Triton X-100, n-hexanol, n-hexane and water solution with hydrochloric acid was prepared. K 3 Fe(CN) 6 was added in as a water-soluble electroactive probe, and its electrochemical behavior was investigated by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). It is found that the H + concentration of the water phase has a great effect on the conductivity of the W/O microemulsion, and hence influences the electrochemical behavior of K 3 Fe(CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This decrease is due to the higher difficulty of charge transporting the microemulsion to the modied electrode surface compared with charge transporting in the aqueous medium, this is a result of the microemulsion not being a continuous medium. 17 The electrochemical behavior of NiHCFNP in microemulsion in the presence of KCl was studied by CV between À0.2 and 1.0 V at a scan range of 20 to 175 mV s À1 . The peak currents were proportional to the scan rate at this range indicating the occurance of an electrochemical process controlled by adsorption, like in aqueous medium.…”
Section: Electrochemical Behavior In Microemulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease is due to the higher difficulty of charge transporting the microemulsion to the modied electrode surface compared with charge transporting in the aqueous medium, this is a result of the microemulsion not being a continuous medium. 17 The electrochemical behavior of NiHCFNP in microemulsion in the presence of KCl was studied by CV between À0.2 and 1.0 V at a scan range of 20 to 175 mV s À1 . The peak currents were proportional to the scan rate at this range indicating the occurance of an electrochemical process controlled by adsorption, like in aqueous medium.…”
Section: Electrochemical Behavior In Microemulsionsmentioning
confidence: 99%
“…Considering the sample preparation for electrochemical measurements, microemulsions have been shown to be a great medium for these applications, in the case of matrices immiscible with water and supporting electrolytes. [14][15][16][17] Using the preparation of microemulsion for sample preparation, it becomes possible to directly analyse matrices, such as biodiesel, without the destruction of organic matter and the need for extraction. Mendonça et al 14 demonstrated, through the redox process of ferrocene and oleic acid, that it is possible to carry out quantitative electroanalytical determinations in microemulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Early observations of its phenotypic and physiological indicators revealed that the pollen was inactive and microspore fertility was low. The anatomic study on the process of differentiation showed that the embryo sac abortion was caused by the abnormal tapetum layer during the embryo sac development of ‘Xiang Yun’ [ 22 ]. However, the underlying mechanism by which genes are responsible for its flower organ development and interactions with plant hormones remains unclear.…”
Section: Introductionmentioning
confidence: 99%